1997
DOI: 10.1007/s001250050844
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin C supplementation of the maternal diet reduces the rate of malformation in the offspring of diabetic rats

Abstract: Although improved metabolic control of maternal diabetes has reduced the rate of complications during pregnancy, the incidence of congenital malformations is still increased in children of insulin-dependent-diabetic (IDDM) mothers [1±4]. The mechanisms by which maternal diabetes disrupts embryonic development are not completely understood, but the risk of fetal malformation is strongly correlated to the maternal glucose concentration [2±4]. Maternal levels of triglycerides, b-hydroxybutyrate and branched chain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(93 citation statements)
references
References 64 publications
2
90
0
1
Order By: Relevance
“…Numerous studies have shown that antioxidants can prevent the developmental defects caused by maternal diabetes in experimental animals [14,18,19,20,21,22,23]. Interestingly, vitamin E was first identified as an essential nutrient for prenatal (but not postnatal) life [39,40].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that antioxidants can prevent the developmental defects caused by maternal diabetes in experimental animals [14,18,19,20,21,22,23]. Interestingly, vitamin E was first identified as an essential nutrient for prenatal (but not postnatal) life [39,40].…”
Section: Discussionmentioning
confidence: 99%
“…mutase, can prevent structural defects caused by high glucose in rodent embryos [13,14,17,18,19,20,21,22,23], this indicates that hyperglycaemia-induced oxidative stress plays a causal role in diabetes-induced congenital defects.…”
mentioning
confidence: 96%
“…Gene expres- Measurement of TBARS Thiobarbituric acid reactive substances (TBARS) are lipid peroxides, and are a major indicator of oxidative stress [34]. TBARS were determined fluorometrically after heating samples with thiobarbituric acid (TBA) [34][35][36]. Briefly, 100 μl of a tissue homogenate of fetal livers at day 17 of gestation was heated to 95°C for 60 min together with 100 μl of SDS solution and 2.5 ml of TBA/buffer reagent (TBARS Assay Kit, ZeptoMetrix, Buffalo, NY, USA).…”
Section: Diabetesmentioning
confidence: 99%
“…Preventive strategies have been examined in laboratory animals based on knowledge of these pathways, in attempts to reduce diabetic embryopathy associated with high glucose levels. For example, birth defect incidence has been reduced in diabetic mice by dietary supplementation with myoinositol (Baker et al, 1990), arachidonic acid (Goldman et al, 1985;Pinter et al, 1986), lipoic acid (Wiznitzer et al, 1999), or antioxidants including vitamin E (Sivan et al, 1996) and vitamin C (Siman and Eriksson, 1997). Torchinsky et al (1997) stimulated uterine immune cells in pregnant mice in an attempt to reduce fetal resorptions associated with diabetes, and made the unexpected observation of significantly reduced malformed fetuses.…”
Section: Maxillary Lengthmentioning
confidence: 99%